PULMONARY AND LIVER DAMAGE DURING TREATMENT WITH ACETAMINOPHEN (PARACETAMOL) - L. I. Dvoretski; A. N. Kovalevskaja; S. E. Kolendo; E. V. Sergeeva (SINAPS LLC, 2016)
This is a case report of pulmonary damage in the form of intestinal pneumonitis with severe respiratory failure during administration of acetaminophen (paracetamol). In addition, significant increase of ALT and AST levels without clinical signs of liver damage was observed in this patient. After glucocorticoids administration regression of radiological abnormal findings in the lungs along with normalization of liver enzymes values were registered. The rarity of interstitial pneumonitis induced by acetaminophen (paracetamol), especially in combination with liver damage, is emphasized. The presented patient history is the first case report of drug-induced hepatopulmonary syndrome during acetaminophen (paracetamol) administration.